2019
DOI: 10.4314/acsj.v27i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of quality protein maize as feed for indigenous chickens in Zimbabwe: A review

Abstract: Indigenous chickens (IC) play an important role in African rural household settings, particularly in improving their livelihoods. However, IC production is characterised by low productivity due to poor quality and quantity of feed, compounded by poor management practises. This dire situation is aggravated by the fact that IC are raised under extensive systems, supplemented with meagre grain supplements. They are a hardy poultry species and as a result most farmers assume that their nutritional requirements can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Later on, breeding o2 mutants with hard vitreous kernels and retaining the high lysine content has led to the development of Quality Protein Maize (QPM). The nutritional benefits of QPM have been well documented in feeding trials 7 , 8 . A number of QPM conversion programs have been successfully accomplished 9 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Later on, breeding o2 mutants with hard vitreous kernels and retaining the high lysine content has led to the development of Quality Protein Maize (QPM). The nutritional benefits of QPM have been well documented in feeding trials 7 , 8 . A number of QPM conversion programs have been successfully accomplished 9 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Two major sources of chicken meat are one fast growing commercial hybrid (broiler) and other one slow growing native chicken. Indigenous chicken production is characterized by low productivity due to poor quality and poor management practices (Bidi et al, 2019). The consumers preferred indigenous chicken meat and eggs for decade after decade and consumer"s attraction towards indigenous chicken will also remain unchanged in future because of their special flavor, taste and texture (Bithi et al, 2020;Islam et al, 2019;Jamaly et al, 2017;Das et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The QPM is reported to have increased levels of lysine and tryptophan in the endosperm protein, which enhances the biological value of protein close to the milk protein (MOTUKURI, 2019). Only 37% of protein intake from non-QPM is utilized compared to 74% of the same amount of QPM (BIDI et al, 2019). Results of a meta-analysis by GUNARATNA et al (2010) indicated that consumption of QPM leads to a 12% increase in the rate of growth in weight and a 9% increase in the rate of growth in height in infants and young children with mild to moderate undernutrition from populations in which maize is a significant part of the diet.…”
Section: Introductionmentioning
confidence: 99%